METHOD FOR PRODUCING SOL-GEL CONDENSATES BASED ON POLYFUNCTIONAL ORGANOSILANES AND USE THEREOF - KRAUS, HARALD; MECHTEL, MARKUS; MAGER, MICHAEL; YUVA, NUSRET (2002)
The invention relates to a method for producing sol-gel condensates by using aqueous silica sols, in addition to the use thereof for coating inorganic or organic substrates.